Structural, magnetic and microwave properties of bismuth ferrite ceramic with yttrium substitution prepared via modified thermal treatment method - Mustapa Zahari, Rahimah (2021)
Bismuth ferrite (BiFeO3 or BFO) with a perovskite structure is one of the multiferroic materials that shows simultaneous coexistence of antiferromagnetic and ferroelectric properties at room temperature, with antiferromagnetic Néel temperature, TN ~370 °C and ferroelectric Curie temperature, TC ~820–850 °C. Based on previous reports, bulk BFO suffers from high impurity phase due to the difficulty in synthesizing single-phase polycrystalline BFO because of the narrow range stability of temperature region, and weak magnetism. Although BFO materials have been extensively studied in the past few years, there are only few reports on Yttrium (Y) substitution at the Fe-site of BFO system. This thesis reports the effect of Y substitution on the structural, magnetic, and microwave properties of BFO. Also, the effect of different prepared temperatures was studied. Y-substituted bismuth ferrites (BiFe1-xYxO3 with x = 0.0, 0.1, 0.2, 0.3, 0.4 and 0.5) ceramics were synthesized via modified thermal treatment method. Three series of samples (or sample batches) were synthesized via modified thermal treatment method. The samples were calcined at 550 °C and sintered at three different temperatures. Batch-1 samples, Batch-2 samples and Batch-3 samples were sintered at 600 °C, 650 °C and 700 °C, respectively. The structural, magnetic and microwave properties of BiFe1-xYxO3 samples were characterized by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), vibrating-sample magnetometer (VSM), and microwave network analyzer (MNA). The XRD analysis showed that the BFO sample was matched to rhombohedral structure with R3c space group. A structural transition has been found to occur with increasing Y concentration. For Batch-1 samples, the structural transition has occurred from rhombohedral R3c (x = 0.0) to orthorhombic Pnma (x = 0.1-0.5). For Batch-2 and Batch-3 samples, the structural transition has occurred from rhombohedral R3c (x = 0.0-0.1) to orthorhombic Pnma (x = 0.2-0.4), and finally to cubic Fm-3m (x = 0.5), respectively. FESEM analysis showed clear grain boundaries with well-defined grain structures of BFO. Also, FESEM analysis revealed that Y substitution has decreased the grain sizes of BFO sample. For Batch-1, Batch-2 and Batch-3 samples, the grain sizes decreased from 165 nm to 38 nm; 201 nm to 56 nm and 354 nm to 90 nm, respectively. The highest value of grain size of about 354 nm was observed in the pure BFO sample from Batch-3. In general, the grain sizes of all the samples were increased with increasing sintering temperatures. The magnetic analysis showed that sample x = 0.2 in each sample batches indicated the enhancement of saturation magnetization, Ms. The Ms value at x = 0.2 from Batch-1 and also from Batch-2 was 0.17 emu/g, meanwhile the Ms value at x = 0.2 from Batch- 3 was 3.95 emu/g. The highest remnant magnetization, Mr value of about 1.21 emu/g was observed for sample x = 0.2 from Batch-3. Pure BFO sample from Batch-1 had the highest coercive force, Hc value of 146.08 Oe. The magnetic behavior of BFO samples changed from weak-ferromagnetic to antiferromagnetic with the increase of sintering temperatures. Also, with the increase of sintering temperatures, the hysteresis loops for samples x = 0.1, 0.2, 0.3, 0.4, and 0.5 became larger and the saturation magnetization increased. The microwave properties of all the samples were measured by the MNA at the frequency range between 8 and 12 GHz (X-band). For the one-port method, both the magnitude and phase of the reflection coefficient is good because of the metal-backed termination at end of the sample which will give stronger combined reflection at the front face of the sample. The minimum reflection loss, RLmin of -8.60 dB at 10.54 GHz was observed for sample x = 0.1 from Batch-2 and -5.25 dB at 9.90 GHz for sample x = 0.0 from Batch-3. The 3 mm thick sample of the pure BFO which was sintered at 600 °C indicated the lowest RL of -19 dB at 8 GHz which is much higher compared to the pure BFO sample measured at the thickness of 1 mm. The RLmin reflects the microwave absorption properties of the prepared samples. Therefore, the results suggest that the microwave absorption properties of all the samples can be manipulated by changing the amount of yttrium substitution into BFO compound and the thickness of the samples. Also, the results suggest that sample x = 0.2 as the potential ferromagnetic applications which possess a high value of Ms making it suitable for the fast processing and higher data storage magnetoelectric random-access memories (MERAM) devices.